Smart Phone Buying Behavior and Factors Affecting Buying Decision of Gen Y in Metropolitan Bangkok - Launglaor, Wisanu; Lealaphan, Acharapan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
Results of the study on Smart Phone buying behavior and factors affecting buying decisions of Gen Y in Metropolitan Bangkok found that Gen Y were mostly women earning 5,001-10,000 baht/mo. Their education levels were undergraduate and above. The latest smart phones they bought were iPhone, followed by Samsung. The reasons they bought these brands were preference / good product, feature/design and full function. Gen Y mostly bought smart phones from department stores. Prices of smart phones they bought were more than 20,000 baht. The popular colors were black and white. Most Gen Y still kept the old mobile phone. Gen Y used each mobile phone for 1-2 years. The factors in choosing a smart phone were for using the Internet, speed of data processing, responded to their needs and can support 3G network. Factors in buying a smart phone between Gen Y male and female are were different. Factors in buying a smart phone between Gen Y who have not completed undergraduate studies and Gen Y who completed a Bachelor’s Degree or above were different. Factors in buying a smart phone between Gen Y with different incomes were different as well. From classifying twice by Hierarchical Cluster Analysis and K-Means Cluster Analysis to identify a subgroup (Cluster), the result found 4 subgroups, that were given names based on the respondents and the product factors: "easy to use” group, "must have” group,” on line socialize” group, and "worthwhileness " group. Test results showed that the amount each group focuses on each factor varied significantly at = 0.05.